Reverse decomposition method vs simplified photovoltaic module electrical model comparison. (February 2018) - Merino, S.; Sánchez, F.; Guzmán, F.; Martínez, J.
Abstract: The resolution of the Photovoltaic modules electrical using mathematical models can be addressed in different ways. Depending on the degree of precision required, several options are available, which will require more or less computational resources in order to solve it. The simplified models have the advantage that they require less resources than the non-simplified ones. This is possible since some parameters are omitted and, therefore, their effect is consequently discarded. In this sense, the herein proposed Photovoltaic module implicit equation model resolution procedure allows to obtain the characteristic current voltage curves, considering all the implied electrical parameters. Furthermore, it is proved that referred model, in comparison with the simplified one, evidences that this one is providing results with a low percentage of error.